Biophysical study of interaction of chitosan with dipalmitoyl-sn-3-phosphochlorine (DPPC) bilayer - Fang, Ning (2008)
The aim of this thesis is to provide new insights into the physicochemical roles of chitosan in overcoming the cell membrane barrier into target cells which still remain largely unknown.